Application of the modified Kudryashov method to the generalized Schrödinger–Boussinesq equations - Kumar, Dipankar; Kaplan, Melike (Springer Science and Business Media LLC, 2018)
In the paper, the modified Kudryashov method is applied to find new exact solutions for the generalized Schrodinger–Boussinesq equation with the help of symbolic computation package Maple through the complex transform. The obtained solutions have been checked by substituting back into its corresponding equation with the aid of Maple package program.